Environmental justice indicators: Evaluating their effectiveness in identifying at-risk communities for drinking water violations - Rae Cade; Danlin Yu; Kyle Whyte; Pankaj Lal; Cortni Borgerson (Cleaner Water)
Despite improvements to environmental protection initiatives, millions of Black, Indigenous, and other people of color (BIPOC) continue to live in communities that are disproportionately affected by environmental contamination. Environmental Justice (EJ) screening tools, such as CalEnviroScreen, EJ Map, and PennEnviroScreen, have been developed to help state and federal governments gauge the extent of EJ in their jurisdictions. These screening tools have propelled the EJ advocacy initiative, illustrating the historic and ongoing disproportionate effects of contamination in many BIPOC communities. Yet, screening tools and their indicators vary, and we must understand how these tools and indicator choices differently identify at-risk communities, including those facing drinking water violations. We investigate how indicator choices differently identify and affect communities facing such violations. Specifically, we examine how EJ screening tools differently identify at-risk communities experiencing drinking water violations, which indicators drive these differences, and how indicator choice affects community identification. Our analysis reveals that EJ screen indicators preferentially identify at-risk, low-income, unemployed, BIPOC renters. However, additional indicators such as middle-income and food insecurity/SNAP can expand identification to ensure actions reach neglected communities. By developing and enhancing EJ screening tools, we can better determine which drinking water violations are present, identify who is being affected by them, and better direct our mitigation efforts to communities in need of assistance.